Moderasi Beragama dalam Pendidikan Islam di Indonesia - Devi Indah Sari; Ahmad Darlis; Irma Sulistia Silaen; Ramadayanti Ramadayanti; Aisyah Al Azizah Tanjung (Journal on Education, 2023)
Al-Quran is the holy book of Muslims whose contents are very relevant for all times and places (mashalih li kulli Zamanin wa eatin), one of the interesting conceptions of the Koran is about religious moderation. Religious moderation is a theory that contains the idea of ​​being moderate, fair and mediocre in every aspect of life in this world. Both are moderate in Aqidah, Worship, Muamalah/akhlaq, or moderate in Tasyri' (Sharia Formation). Meanwhile, the term religious moderation is always described in the Koran in a large set of various types of characters, including the character of honesty, intertwined mindset, love, and flexible character, which are integrated with each other, holistic and universal, all of which cannot be separated, interrelated. strengthen and benefit. Religious moderation is also emphasized in Islamic education in Indonesia, especially in aspects of learning techniques and content of material which includes material from the Koran hadith, Fiqh of Worship, Aqidah Akhlaq, Sharia (Islamic law) and Islamic Dates (Islamic history). All of the Islamic education materials above are presented in ways and techniques that uphold high values ​​and the principles of moderation in religion so as to foster character and personality that has flexibility, love, pluralism, concern and is able to act fairly and in the middle in dealing with every problem that comes and more and more a plurality generation that upholds the principle of goods and mutual respect for the principle of difference, more and more generations are emerging who love diversity in diversity so that Indonesia becomes a country that is Baldatun Thoyyiibatun Wa Rabbun Ghafur.